STRUCTURE AND techological improvments of tmbs diodes - V. S. Kotov; N. F. Golubev; V. E. Borisenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
An improved structure and technological process of trench MOS barrier Schottky (TMBS) diodes are developed and studied by 2D-simulation. The experiments performed demonstrated simplification of the technology by elimination of one photolithography and improvement of the diode parameters.